Introduction of a New B3Y-Fetal Potential in the Semimicroscopic Analysis of the 15N + 27Al Nuclear System - Soldatkhan, D.; Mauyey, B.; Baratova, A.A.; Makhanov, K.M. (Karagandy University of the name of academician E.A. Buketov, 2025)
The experimental data analysis of the low-energy elastic scattering process in the 15N+27Al nuclear system used a new microscopic approach. In the microscopic analysis, new B3Y-Fetal potentials, calculated using the variational method with lower-order constraints (LOCV) in two-body matrices, were applied. Based on the double folding model (DFM), the CDM3Y2-Paris, CDB3Y2-Fetal, and CDB3Y3-Fetal microfolding po tentials were constructed by adjusting density-dependent parameters C, α, β, and γ. These density-dependent parameters were introduced based on the effective nucleon-nucleon (NN) interaction and the form factor of the nucleon density distribution of the colliding 15N and 27Al nuclei. The uniqueness of the analysis lies in the fact that the introduced density-dependent parameters were calculated using the optimal value of the K — compressibility factor, which characterizes the saturation properties of the nuclear medium. The optimal pa rameter sets for the optical and folding potentials were determined from the results of the optical model (OM) and DFM analyses. The theoretical cross-sections of elastic scattering obtained from phenomenological and microscopic analyses were found to describe the experimental data well. In the semi-microscopic analysis, the effectiveness of the B3Y-Fetal folding potential was determined. Based on the analysis of the experi mental data of elastic scattering, it was concluded that the saturation properties of nuclear matter can be de termined more accurately. The low-energy elastic scattering reaction in the 15N+27Al nuclear system is im portant for studying the properties of materials and nuclear fuels. This study of the nuclear process contrib utes to the development of future nuclear materials and energy technologies.
15N + 27Al ядролық жүйені жартылай микроскопиялық талдау кезінде жаңа B3Y-Fetal потенциалын енгізу
Введение нового потенциала B3Y-Fetal при полукомикроскопическом анализе ядерной системы 15N + 27Al
Keywords: microscopic analysis; elastic scattering; double folding model; B3Y-Fetal potential; nucleon densi ty distribution